On shear fracture and morphological features of fused filament fabrication based almond skin reinforced PLA structures. Issue 3 (3rd July 2022) - Singh, Rupinder; Kumar, Ranvijay; Singh, Mohit; preet, Pawan
ABSTRACT: The polylactic acid (PLA) composite-based 3D printed functional prototypes have been widely explored for preparation of biomedical scaffolds with fused filament fabrication (FFF). But hitherto little has been reported on the use of the almond skin (AS) as reinforcement in PLA matrix for scaffolding applications with improved shear modulus (SM). In this study composite of PLA and AS was subjected to pull-out test to ensure SM and modulus of toughness (MOT), surface hardness and morphological investigations for use as scaffold. The results of study show that during pull-out test, maximum shear strength at peak (PSS) as 22.85MPa; maximum shear strength at break (BSS) as 20.56MPa was observed for samples printed with infill density (ID) 100%, infill angle (IA) 45 ° and infill speed (IS) 90 mm/s (on open source FFF setup). The maximum MOT as 25.50 MPa was noticed for sample printed at ID 60%, IA 45 ° and IS 50 mm/s. Further maximum SM as 21.80 MPa was observed for samples printed at ID 60%, IA 60 ° and IS 70 mm/s. The results have been supported by photo-micrographic analysis; surface hardness analysis; Taguchi and response surface methodology based historical data approach for optimisation of pull-out properties.